Biogeochemical status of the Paleo-Pacific Ocean: clues from the early Cambrian of South Australia. Issue 7 (3rd October 2021) - Hall, P. A.; McKirdy, D. M.; Halverson, G. P.; Jago, J. B.; Collins, A. S.
Abstract: The Ediacaran–Cambrian transition was a time of profound reorganisation of the biosphere, coinciding with the assembly of Gondwana and increasing atmospheric and oceanic oxygenation. The lower Cambrian marine sediments of the Stansbury Basin, South Australia, were deposited at low northern paleolatitudes on the western margin of the emerging Pacific Ocean. Here we report results of a multi-pronged investigation employing trace and rare earth element (REE) abundances, total organic carbon (TOC) contents and pyritic sulfur isotopic compositions (δ 34 Spy ) in carbonaceous shales from three formations within the Normanville and Kanmantoo groups (sequences Є1.2 to Є2.2). TOC ranges from ≤0.5 wt% in the Emu Bay Shale, through 0.4–1.9 wt% in the Talisker Formation, to 0.2–2.6 wt% in the Heatherdale Shale. Covariance is demonstrated between trace elements and organic matter, with comparative uranium enrichment in the Heatherdale Shale likely linked to increased primary productivity. Heavy REEs and yttrium are typically more depleted than light REEs. Provenance appears to evolve through the upper Normanville sediments into the Kanmantoo Group, corroborating published detrital zircon interpretations that suggest an increasing dominance of southerly derived sources. The prevailing paleoredox regime for the Heatherdale Shale and the Talisker Formation was dysoxic, evolving into progressively more reducing conditions up section, the latter exhibiting a secular decline in δ 34 Spy (from +10 to −11‰ VCDT). Conversely, redox proxies concur in demonstrating that the basal fossiliferous Emu Bay Shale accumulated beneath an oxic water column. Comparison of trace element and REE distributions with those of slightly older sequences on the Yangtze Platform, South China, reveals striking similarities, implying that the trace element chemistry of the Paleo-Pacific and Asian oceans was homogeneous. KEY POINTS: Trace and rare earth element, total organic carbon and sulfur isotopic data provide a multi-faceted profile of shales from three formations in the Stansbury Basin. The prevailing paleoredox regime for the Heatherdale Shale and Talisker Formation was dysoxic, whereas the basal Emu Bay Shale accumulated beneath an oxic water column. The strong covariance between TOC and normalised Mo, V and U in these shales highlights the evolving bioproductivity and oxygenation of the early Cambrian ocean. Similar element signatures in lower Cambrian black shales, South China, reflect the homogeneous biogeochemistry of the Paleo-Pacific and Asian oceans.